LEAN METHODOLOGY IMPLEMENTATION IN THE EMERGENCY DEPARTMENT OF A UNIVERSITY HOSPITAL: MANAGEMENT AND SUSTAINABLE DEVELOPMENT. - da Rocha, Cristiano Rossa; Rempel, Claudete; Batista Santana, João Carlos; Ferranti, Eliziane; Furlan Inchauspe, Juciane Aparecida; dos Santos, Suimara; Chassot, Maicon Daniel; Santarém, Michelle Dornelles (Texto & Contexto Enfermagem, 2023)
Objective: to describe the implementation of the Lean Methodology in an emergency department and its contribution to sustainable and quality management. Method: this is a methodological study carried out between October 2018 and January 2022 in the adult emergency department of a public university hospital in southern Brazil, analyzing the results before and after the implementation of the Lean Methodology. The study followed the model and standards adopted by the Standards for Quality Improvement Reporting Excellence 2.0 (SQUIRE) for the description of improvement cycle standards. Results: with the implementation of this methodology, actions were developed, such as innovations in work routines, both care and management, changes in patient reception with risk classification, construction of units for patient care and allocation, daily interdisciplinary meetings (huddle), full contingency plan, hospital discharge routines, external transfers, changes in the communication process with users and professionals, among other actions. Conclusion: the use of the Lean Methodology has resulted in a reduction in occupancy, which has helped to optimize health resources and ensure quality care and management practices. This reduction is believed to be proof of sustainable management in health services and contributes to reducing socio-economic inequalities.